Non-Operative Rehabilitation Principles for Use in Individuals with Acetabular Dysplasia: A North American Based Delphi Study - Ashley E. Disantis; RobRoy L. Martin; Keelan Enseki; Victoria Spaid; Michael McClincy (North American Sports Medicine Institute, 2023)
# Background Acetabular dysplasia (AD) is defined as a structurally deficient acetabulum and is a well-recognized cause of hip pain in young adults. While treatment of severe AD with a periacetabular osteotomy has demonstrated good long-term outcomes, a trial of non-operative management is often recommended in this population. This may be especially true in patients with milder deformities. Currently, there is a paucity of research pertaining to non-operative management of individuals with AD. # Purpose To present expert-driven non-operative rehabilitation guidelines for use in individuals with AD. # Study Design Delphi study # Methods A panel of 15 physiotherapists from North America who were identified as experts in non-operative rehabilitation of individuals with AD by a high-volume hip preservation surgeon participated in this Delphi study. Panelists were presented with 16 questions regarding evaluation and treatment principles of individuals with AD. A three-step Delphi method was utilized to establish consensus on non-operative rehabilitation principles for individuals presenting with AD. # Results Total (100%) participation was achieved for all three survey rounds. Consensus, defined a piori as > 75%, was reached for 16/16 questions regarding evaluation principles, activity modifications, appropriate therapeutic exercise progression, return to activity/sport criteria, and indications for physician referral. # Conclusion This North American based Delphi study presents expert-based consensus on non-operative rehabilitation principles for use in individuals with AD. Establishing guidelines for non-operative management in this population will help reduce practice variation and is the first step in stratifying individuals who would benefit from non-operative management. Future research should focus on patient-reported outcomes and rate of subsequent surgical intervention to determine the success of the guidelines reported in this study. # Level of Evidence Level V